2002
DOI: 10.1021/ol020015x
|View full text |Cite
|
Sign up to set email alerts
|

Base-Pairing Systems Related to TNA:  α-Threofuranosyl Oligonucleotides Containing Phosphoramidate Linkages1

Abstract: (3'NH)- and (2'NH)-TNA, two isomeric phosphoramidate analogues of TNA (alpha-threofuranosyl-(3'-->2') oligonucleotides), are shown to be efficient Watson-Crick base-pairing systems and to undergo intersystem cross-pairing with TNA, RNA, and DNA. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 20 publications
(28 reference statements)
0
35
0
4
Order By: Relevance
“…[165,166] A. Eschenmoser Aufsätze rungssystemen zukommt, [173,174] haben wir vergleichende Versuche über templatkontrollierte Ligationen von TNALiganden an TNA-, RNA-und DNA-Templaten angestellt (Abbildung 65). [175,176] Dabei wurde auch von der im Vergleich zu Adenin hçheren Paarungseffizienz des 2,6-Diaminopurins [177,135] sowie der im Vergleich zur Hydroxygruppe hçheren Nukleophilie der Aminogruppe bei solchen Ligationsreaktionen [178,179] Gebrauch gemacht. Die Ligationsexperimente der Abbildung 65 (EDC = wasserlçsliches Carbodiimid) offenbaren eine drastische Beschleunigung der Ligation bei Ersatz von Adenin durch 2,6-Diaminopurin in den beiden TNA-Liganden mit sowohl dem TNA-als auch dem RNA-Templat; nur mit dem unter den gewählten Reaktionsbedingungen "toten" DNA-Templat bleibt der Ersatz ohne Wirkung.…”
Section: L-a-threofuranose-nukleinsäure ("Tna")unclassified
“…[165,166] A. Eschenmoser Aufsätze rungssystemen zukommt, [173,174] haben wir vergleichende Versuche über templatkontrollierte Ligationen von TNALiganden an TNA-, RNA-und DNA-Templaten angestellt (Abbildung 65). [175,176] Dabei wurde auch von der im Vergleich zu Adenin hçheren Paarungseffizienz des 2,6-Diaminopurins [177,135] sowie der im Vergleich zur Hydroxygruppe hçheren Nukleophilie der Aminogruppe bei solchen Ligationsreaktionen [178,179] Gebrauch gemacht. Die Ligationsexperimente der Abbildung 65 (EDC = wasserlçsliches Carbodiimid) offenbaren eine drastische Beschleunigung der Ligation bei Ersatz von Adenin durch 2,6-Diaminopurin in den beiden TNA-Liganden mit sowohl dem TNA-als auch dem RNA-Templat; nur mit dem unter den gewählten Reaktionsbedingungen "toten" DNA-Templat bleibt der Ersatz ohne Wirkung.…”
Section: L-a-threofuranose-nukleinsäure ("Tna")unclassified
“…[4] Nitrogenous analogues of TNA in which either O3' or O2' is substituted by an NH group are equally efficient Watson-Crick base-pairing systems; they also crosspair with TNA, RNA, and DNA. [5] It was recently shown that certain DNA polymerases are able to copy a TNA template sequence, albeit of limited length and at a slower rate than with a DNA template. [6] Moreover, a DNA polymerase has been identified that is capable of significant TNA synthesis.…”
mentioning
confidence: 99%
“…These results are in contrast to the ease of synthesis and isolation of the oxygen congener, GNA [3]. Apparently, the introduction of the N-atom converts GNA into a potential constituent of a reaction mixture with mainly catalytic power [1].…”
Section: Synthesis Of Protected (R)-and (S)-2'-aminopropyl Nucleosidementioning
confidence: 88%